Plurality and equality in the Learning Communities - Mimar Ramis-Salas (Intangible Capital, 2015)
Purpose: to present empirical evidence of the success generated as a result of the types of organization of the centres and the classrooms in the CA. The inclusion of the plurality of voices of families from very different origins allows for an education that based on the plurality and diversity manages to achieve a greater equality in the results of all children. Design/methodology/approach: the present article is based on 1) review of the scientific literature in journals selected in the Journal Citation Reports about the types of participation of migrant families and from cultural minorities and their effect on the education of their children; and 2) on the collection of testimonies of migrant and cultural minority families through qualitative techniques. Findings and Originality/value: empirical evidence is presented about how the types of management and organization of the families participation in the classroom and the school of Learning communities maximize the plurality of voices (migrant and cultural minority families) and contribute to improve the results of the children of the social groups who are most underprivileged and who obtain a greater improvement in the results levelling them with those of the mainstream society. Research limitations/implications: complexity to achieve a climate of ideal egalitarian dialogue in the framework of the communicative research data collection techniques Social implications: the article emphasizes the fact that evidence based actions achieve social and educational transformation, contributing to respond to the objectives of Europe 2020 to achieve more inclusive societies. Originality/value: how through implementing certain forms of classroom and school organization based on the inclusion of the plurality of voices, we contribute evidence of the improvement of the management of the center and the transformation of the relations with the community, beyond the educational success.